The ABCB6 mutation p.Arg192Trp is a recessive mutation causing the Lan− blood type. Issue 2 (10th September 2012) - Saison, C.; Helias, V.; Peyrard, T.; Merad, L.; Cartron, J.‐P.; Arnaud, L.
<x xml:space="preserve">Abstract</x> Background and Objective The membrane transporter ABCB6 has recently been shown to carry the high‐frequency red‐blood‐cell (RBC) antigen Lan. All the Lan− individuals genotyped so far have inherited two recessive null mutations in ABCB6. The finding of a family with the Lan− blood type occurring in two successive generations prompted this study. Methods Mutations in ABCB6 were searched by Sanger sequencing of exons and flanking intronic regions. Expression analysis of the Lan antigen was carried out by serology and flow cytometry. PCR‐RFLP genotyping and Western blot analysis were also applied. Results All the Lan− members of this family were homozygous for c.574C>T, p.Arg192Trp in ABCB6 while the Lan+ members were heterozygous for this missense mutation encoded by the SNP rs149202834. Homozygosity for p.Arg192Trp was associated not only with absence of the Lan antigen, but also of the ABCB6 transporter in RBC membrane. The complete absence of Lan expression resulting from p.Arg192Trp homozygosity was confirmed by the subsequent identification of five unrelated Lan− individuals who were homozygous for this mutation and who developed an anti‐Lan. We also provide evidence that three other single amino acid mutations in ABCB6 (c.826C >T, p.Arg276Trp; c.85_87delTTC, p.Phe29del; c.1762G >A, p.Gly588Ser) may also define ABCB6 null alleles. Conclusion p.Arg192Trp is the first ABCB6 missense mutation causing the Lan− blood type and appears to be a relatively frequent cause of this rare blood type. Like the previously reported frameshift, nonsense and essential splice‐site mutations in ABCB6, this missense mutation is recessive and defines an ABCB6 null allele. Other single amino acid mutations in ABCB6 may also cause the Lan− blood type.